1992
DOI: 10.3382/ps.0711357
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Poultry Fat and Gastrointestinal Transit Time of Feed and Fat Utilization in Broiler Chickens

Abstract: An experiment was conducted with broiler chicks to determine the effect of 0, 5, 10, and 20% supplemental poultry fat and age on gastrointestinal transit time (GTT) and the effect of supplemental fat on fat utilization and growth. Mean GTT, measured with chromic oxide or ferric oxide, was not affected by supplemental fat. There was a curvilinear relationship (rising ogive) between mean GTT and age. It increased from an estimated lower plateau of 170 min to an upper plateau of 211 min with the inflexion point a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
14
0
3

Year Published

1999
1999
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(25 citation statements)
references
References 32 publications
8
14
0
3
Order By: Relevance
“…Era esperado que a adição de óleo de soja promovesse maior tempo de retenção do alimento no sistema digestório, pois, segundo Swenson & Reece (1996), a gordura dietética estimula a liberação do hormônio colicistoquinina, que diminui a velocidade de esvaziamento do sistema digestório, no entanto, reduziu linearmente o tempo de trânsito, contrariando os resultados observados por Rao & Clandinin (1970), Mateos & Sell (1981) e Mateos et al (1982). Em contrapartida, estudos de Tuckey et al (1958), Golian & Polin (1984) e Golian & Maurice (1992) não mostraram qualquer evidência de que a adição de gordura aumenta o tempo de trânsito do alimento em frangos de corte.…”
Section: Resultsunclassified
See 2 more Smart Citations
“…Era esperado que a adição de óleo de soja promovesse maior tempo de retenção do alimento no sistema digestório, pois, segundo Swenson & Reece (1996), a gordura dietética estimula a liberação do hormônio colicistoquinina, que diminui a velocidade de esvaziamento do sistema digestório, no entanto, reduziu linearmente o tempo de trânsito, contrariando os resultados observados por Rao & Clandinin (1970), Mateos & Sell (1981) e Mateos et al (1982). Em contrapartida, estudos de Tuckey et al (1958), Golian & Polin (1984) e Golian & Maurice (1992) não mostraram qualquer evidência de que a adição de gordura aumenta o tempo de trânsito do alimento em frangos de corte.…”
Section: Resultsunclassified
“…Com relação à idade das aves, os resultados relativos à diferença encontrada no tempo de trânsito são concordantes daqueles observados por Golian & Maurice (1992), que encontraram correlação positiva do TT com a idade. Segundo esses autores, há um patamar baixo (171 minutos), passando para um mais alto (221 minutos), de quatro para seis semanas, apresentando ponto de inflexão aos 22 dias de idade.…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Experimental results showed that the consumption of Ca-PFA had the physiological effect on digestive system and increased metabolism of the chickens. According to Gollian and Maurice (1992) cited by Zulkifli (2007), the high metabolism required constantly food availability, it is believed that fat content in diet slow the passage rate of the diet in the intestine, resulting in longer nutrient absorbtion time. Table 2 presents the effect inclusion of Ca-PFA on final body weight.…”
Section: Growth Performancementioning
confidence: 99%
“…Lastly, it can also be hypothesized that increased intestinal length and weight affects transit time of the digesta through the gut. However, in young broiler chickens (7 to 42 d of age), the transit time was not affected by dietary fat inclusion up to 20% (Golian and Maurice, 1992). Therefore, it seems unlikely that increased intestinal length and weight affect transit time through the gut.…”
Section: Discussionmentioning
confidence: 96%